On Quasi-Commutative KK-algebra. (3rd March 2016) - Asawasamrit, Suphawat; Promsakon, Chanon
Abstract: In this paper, we define the notions of commutative and quasi-commutative in KK-algebras. We give several characterizations and the extensive theorems for the commutative and quasi-commutative. Moreover, we show the relation between p- semisimple and quasi-commutative in KK-algebras.